Upadacitinib: Mechanism of action, clinical, and translational science - Mohamed‐Eslam F. Mohamed; Sumit Bhatnagar; Julie M. Parmentier; Priscila Nakasato; Peter Wung (Wiley, 2024)
Abstract Upadacitinib is a selective Janus kinase (JAK) inhibitor which is approved by the US Food and Drug Administration, the European Medicines Agency, as well as other agencies around the world for the treatment of several chronic inflammatory diseases, including rheumatic, dermatologic, and gastrointestinal diseases. Through inhibition of JAK, upadacitinib inhibits phosphorylation of downstream effector proteins, which consequently inhibits cytokine signaling for key pathways involved in inflammatory diseases. Upadacitinib more potently inhibits JAK1 than other JAK isoforms. The pharmacokinetics, pharmacodynamics, efficacy, and safety of upadacitinib were characterized in many clinical trials, which demonstrated the superiority of upadacitinib treatment over placebo or an active comparator in rheumatoid arthritis, psoriatic arthritis, ankylosing spondylitis, non‐radiographic axial spondyloarthritis, atopic dermatitis, Crohn's disease, and ulcerative colitis. The safety profile of upadacitinib supported a favorable benefit-risk profile across all the approved indications. In this article, we review the mechanism of action of upadacitinib and describe how the JAK-STAT (Janus kinase-signal transducers and activators of transcription) pathway is involved in the pathogenesis of several chronic and progressive immune‐mediated inflammatory diseases. In addition, this review also provides an overview of key clinical trials that were conducted as well as relevant data which supported the clinical development of upadacitinib and informed the recommended dose(s) in each of the approved indications.